His Majesty King Bhumibol Adulyadej’s Musical Genius: A Case Study of the Arrangement of 41 Royal Compositions with Lyrics for Choir - Saibunmi , Skowrung; Laovanich, Vitchatalum; Laovanich, Monsikarn (Rangsit Music Journal, 2020)
This research paper aims to investigate the process of arranging 41 of King Bhumibol Adulyadej's royal compositions with lyrics for choir. The study employs a qualitative method in order to understand the process of arranging these royal compositions. The instruments used for information gathering in this study were interviews. The participants were selected using purposeful sampling. The interviewees were three arrangers who adapted 41 royal compositions for choir. The result showed that the arrangement needs to follow the regulations of the Bureau of the Thai Royal Household, select styles for arrangement for each piece, structure the piece, create harmonic lines, add colour to each piece, and create an introduction, instrumental section, and ending.